User Interface (UI) Design and User Experience (UX) for Mobile-based Quranic Memorizing using the Lean UX - Muhammad Arkoun Rifki; Kholid Haryono (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2023)
The interest of the Muslim community in memorizing the Qur'an is increasing today. The appreciation for the memorizers is also getting higher with the many opportunities for scholarships and other achievements from various institutions, especially universities. Memorizing activities are usually taught at Islamic boarding schools using special manuscripts and accompanied by teachers directly. This luxury cannot be enjoyed by the Muslim community, which is increasingly having high mobility. Therefore, it is an opportunity to present digital memorization manuscripts installed on their devices. In addition, the memorization method taught in Islamic boarding schools is also based on the instructions of the Mushaf and the input from the memorizers has shown that the tikrar method is the most widely used. This study will propose a digital mushaf design for memorizing using the tikrar method which makes it easy for the memorizers. The method used is Lean UX by providing a prototype based on the results of the memorization manuscript review and the currently available application of the Qur'an. This prototype was immediately reviewed by the memorizers to get the appropriate design. The results of the design were tested using the Usability Testing and Important Performance Analysis (IPA) methods in order to gain ease of use and user acceptance with the proposed design. The results show positive review results by achieving an easy, intuitive, and efficient design with a usability score of 79.8 which means it is quite good.Keywords: Al Qur’an memorization, Usability testing, Important Performance Analysis, Lean UX, Tikrar method.